(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Relevance of the topic: Most students studying at medical institutes of our republic want to study abroad, they believe that the reason for this is the educational system and the requirements of foreign institutions, as well as the opportunities created. Goal: To raise the quality of student education in medical institutes of our republic to the level of foreign institutes. Expected result: Training of competitive quality personnel.